2016
DOI: 10.1080/07347332.2016.1252823
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of group intervention for bereaved siblings after pediatric cancer death

Abstract: This study evaluated the feasibility (acceptability, recruitment, retention rates, treatment fidelity, and outcome measures) of implementing a manualized group intervention for bereaved siblings after pediatric cancer death. A convenience sample of 10 siblings participated. The intervention consisted of eight 2-hour sessions that focused on strategies for coping with grief, relationships, and emotional growth. Positive outcomes were obtained with respect to acceptability, recruitment, retention rates, and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(61 citation statements)
references
References 60 publications
0
60
0
Order By: Relevance
“…Characteristics of the included studies are shown in Table . Ten studies addressed parental bereavement, and 14 studies addressed sibling bereavement . To our knowledge, the 24 included studies published between 1983 and 2017 are based on 13 research projects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the included studies are shown in Table . Ten studies addressed parental bereavement, and 14 studies addressed sibling bereavement . To our knowledge, the 24 included studies published between 1983 and 2017 are based on 13 research projects.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, the 24 included studies published between 1983 and 2017 are based on 13 research projects. Six projects were conducted in the USA, 2 in Sweden, 2 in Canada and the USA, and 1 in Canada, Japan, and Great Britain, respectively. Twenty studies reported cross‐sectional results of childhood cancer bereavement, with outcomes being assessed between 0 and 17 years after loss.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations